1991
DOI: 10.1007/bf01606500
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical demonstration of keratins 8 and 14 in benign tumours of the skin appendage

Abstract: The expression of keratins 8 and 14 was investigated immunohistochemically by the avidin-biotin-peroxidase (ABC) method using formalin-fixed paraffin-embedded specimens from 42 tumours of human skin appendages. Results were compared with the staining of 34 specimens from normal skin and skin appendages adjacent to the tumours. Keratin 14 was detected by the monoclonal antibody (mAb) 312C8-1, and was found in the basal cells of the epidermis, the outer root sheaths of hair follicles, and the peripheral cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
5
16
2
Order By: Relevance
“…This result agrees with Setterfield's report (21). CK-L is known to be immunopositive in secretory cells, such as eccrine gland (22)(23)(24). Degenerated sweat gland was shown the decreased immunoreactivity for CK-L.…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with Setterfield's report (21). CK-L is known to be immunopositive in secretory cells, such as eccrine gland (22)(23)(24). Degenerated sweat gland was shown the decreased immunoreactivity for CK-L.…”
Section: Discussionsupporting
confidence: 92%
“…Real-time PCR confirmed that primary SSG3 expressed a similar level of PPARγ as the immortalized sebocyte line SEB-1 [15] (Figure 2b). However, SEB-1 expresses Keratin 8, a protein associated with skin appendages tumors [28], whereas SSG3 cells do not express Keratin 8 (Figure 2a), akin to sebaceous gland in vivo [29]. Additionally, SSG3 cells express other markers of sebocytes such as Blimp1 and epithelial membrane antigen EMA/Muc1 (Additional file 1: Figure S1c, d and e).…”
Section: Resultsmentioning
confidence: 99%
“…The starting point of our study was the discovery of a novel type II epithelial keratin, K1b, which proved to exhibit virtually no expression site in the human body other than in luminal cells of the entire eccrine sweat duct. Using the K1b expression in these cells as a reference pattern for co-expression studies with antibodies against the plethora of sweat gland keratins known from previous studies (Kurokawa et al, 1988;Broekaert et al, 1990;Wollina et al, 1990a, Moll and Moll, 1991, 1992Tsubura et al, 1991;Wollina, 1991;Yoneda et al, 1991;Eckert et al, 1992;Watanabe et al, 1993Watanabe et al, , 1994Demirkesen et al, 1995;Biernat et al, 1996;Onishi and Watanabe, 1997;Schö n et al, 1999;Onishi et al, 2002), as well as of further keratins, we were able to provide new insights into the differentiation pathways and the function of both the peripheral and the luminal cell layers of the sweat duct of eccrine sweat glands.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies were primarily selected on the basis of a large body of previous investigations on the keratin expression in the adult human eccrine sweat gland. Collectively, these studies revealed the expression of an amazingly large number of heterogenous keratins, such as K1, K10, K5, K14, K15, K6, K16, K17 as well as K8, 18, K19, and K7, in this rather small secretory skin appendage (Kurokawa et al, 1988;Broekaert et al, 1990;Wollina et al, 1990a;Moll, 1991, 1992;Tsubura et al, 1991;Wollina, 1991;Yoneda et al, 1991;Eckert et al, 1992;Watanabe et al, 1993Watanabe et al, , 1994Demirkesen et al, 1995;Biernat et al, 1996;Onishi and Watanabe, 1997;Schö n et al, 1999;Onishi et al, 2002). It should be mentioned, however, that in none of the previous studies has the full complement of these keratins been investigated simultaneously and in all segments of the sweat gland.…”
Section: Figurementioning
confidence: 95%